Formation of the subjectivity at students in educational process of higher education - Aiman Koblanova, Damira Sovetkanova, Zhanar Seysenbayeva,; Muhtar, Yermekbayev (Opción, 2019)
This article analyzes the questions about diversity and multi-functionality of the phenomenon of subjectivity in the context of cross-disciplinary approach. As a result, the process of personal and professional development of students at the stage of self-realization determines the next stage of pedagogical activity- the stage on formation of initial skills of professional competence at the specialist. In conclusion, formation of subjectivity at students in higher education institution can be considered as the determined, probabilistic, operated and spontaneous processThis article analyzes the questions about diversity and multi-functionality of the phenomenon of subjectivity in the context of cross-disciplinary approach. As a result, the process of personal and professional development of students at the stage of self-realization determines the next stage of pedagogical activity- the stage on formation of initial skills of professional competence at the specialist. In conclusion, formation of subjectivity at students in higher education institution can be considered as the determined, probabilistic, operated and spontaneous process